A Comparison of Acute Complications and Mortality Between Geriatric Knee and Hip Fractures: A Matched Cohort Study. Issue 21 (1st November 2021) - Wolfstadt, Jesse I.; Atrey, Amit; Nowak, Lauren L.; Stavrakis, Alexandra; Melo, Luana T.; Backstein, David; Schemitsch, Emil H.; Nauth, Aaron; Khoshbin, Amir
Abstract : Introduction: To compare acute complication and mortality rates for operatively treated, closed, isolated, low-energy geriatric knee fractures (distal femur [DFF] or tibial plateau [TPF]) with hip fractures (HFs). Methods: This is a retrospective cohort study using the American College of Surgeons National Surgical Quality Improvement Program. We identified all patients ≥ 70 years from 2011 to 2016 who underwent surgery for DFF, TPF, or HF. We recorded patient demographics, functional status, complications, and mortality. We matched DFF:TPF:HF patients on a 1:1:10 ratio based on age, sex, body mass index, baseline functional status, and comorbidity. We used the chi square, Fisher exact, and Mann Whitney U tests to compare unadjusted differences between groups and multivariable logistic regression to compare the risk of complications, readmission, or death while adjusting for relevant covariates. Results: When compared with HF, patients in the DFF and TPF groups had longer length of stay and time to index surgery and were more likely to be discharged home. The rate of deep vein thrombosis was significantly higher in the TPF group (TPF = 3.9%, DFF = 1.3%, and HF = 1.2%, P = 0.005). Conclusion: Geriatric knee fractures pose a similar risk of acute complications, mortality, and readmission compared with patients with HF. Future studies investigating strategies to decrease risk in this patient cohort are warranted. Level of Evidence: Therapeutic Level III